Elementos para uma tipologia de gênero da atuaç\~ao estatal: Vis\~oes do estado sobre as mulheres e políticas públicas no Brasil - Janine Mello; Danusa Marques (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– This text presents a typology proposal for State visions on representations of women as references to shape the public action. The theoretical framing of this proposal assumes that there are many disputes among narratives of state agents, considering the patriarchal foundations of political institutions. Many works on this issue correctly criticize, in our opinion, the State's maternalist framework of women on social development policies, reinforcing stereotypes and the sexual division of care. We agree with this approach, but we also present other views that the State can take when it comes to policies that have women as the target audience. From a formal analysis of selected policies, we indicate that, in addition to this reproductive vision, it is also possible to identify a productive vision (which fits women exclusively as labor in the labor market), an inclusive vision (which prioritizes to consolidate citizenship rights for women in an expanded approach to fight gender inequality) and a reactive vision (which incorporates women already in the course of policy implementation as a later incremental adjustment). These categories do not seek to completely exhaust the possibility of visions of the State on women. Our goal is to understand the policy designs implemented in the last decades in Brazil identifying more effective and incisive measures to fight gender inequality in the country.
Keywords: H11; 330; gender; public policies; women; State